Determination of the material model parameters for high pressure densification induced glass inferred through analytical comparison and its ballistic performance as used in composite laminates. (1st January 2023) - Thakur, Nitin; Bharj, Rabinder Singh; Kumar, Pramod; Sharma, Prince; Sharma, Sumit; Bahl, Shashi
Abstract: The Drucker Prager material model, Ductile Damage and Mie-Gruneisen equation of state parameters for high-pressure densification induced glass were derived analytically in the current study by comparing them to the Johnson Holmquist-II (JH-2) model. These parameters were then utilized to simulate the ballistic impact behaviour of bullet-resistant glass in ABAQUS/Explicit and the results were compared to the simulation results using JH-2 model in ANSYS/Autodyn and the results were found in good agreement. Following that, their experimental equivalents were tested for validation prospective. The findings were then compared to conventional bullet-resistant glass. It was found that the new bullet-resistant glass fabricated from layers of high-pressure densification induced glass was superior in strength as compared to the conventional bullet-resistant glass.